(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Number of elderly population is growing very faster all over the world. This growth in elderly population relative to other age groups challenges mostly the existing health services, family relationships and social security. In this article we tried to address the gravity of the issue at family, social and national level. We also examined the parents care scenario in Western World and Asian societies. Observations and conclusions: Our observations revealed that old people from both West and Asia are interested to stay in their home with their children and grandchildren. This is a way to transmit there real life experience to their third generation (grand children) which, however, is very essential for the emotional, humane and psychological development of our future generation of the World. The present day capitalistic attitude is eroding the emotion and affection to the old and a big number of then end up in West and although smaller in Asian countries, but showed increasing trend, end up old homes. There are, however, situations where facilities needed for care of older people who lost their children and sometimes ailing people in native countries where their children living or settled aboard. Taking into consideration of the growing issue and empathic care of those facilities in such situations run following guidelines and ethical rules. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.453-457